A story to tell or not, a glimpse of emergency setting in the low economic country: experience sharing and Review - Das, Sunil Kumar; Twanabasu, Sajal (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Delivering efficient emergency health care in low-income countries presents significant challenges due to various factors, including limited resources, inadequate infrastructure, and socio-economic barriers. This article explores the complexities associated with emergency care delivery in resource-limited settings. Issues such as prehospital care, triage, waiting times, out-of-pocket expenditures, and the implementation of international protocols with limited resources. The lack of access to well-equipped ambulances, trained personnel, and basic first aid knowledge contributes to the difficulties faced in prehospital care. Non-functional triage systems, direct access to emergency rooms, and financial constraints further hinder timely and effective patient care. The implementation of international protocols in settings with limited resources poses additional challenges for healthcare providers and patients.